Aggressive Fibromatosis: Evidence for a Stable Phase. (1998) - Mitchell, Gillian; Thomas, J. Meirion; Harmer, Clive L.
Abstract : Purpose. Aggressive fibromatosis (AF) is an uncommon locally infiltrating benign disease of soft tissue for which treatment comprises complete surgical resection. Radiotherapy can be given postoperatively if the margin is incompletely resected. If the tumour is inoperable radiotherapy provides an alternative treatment. Hormone therapy and cytotoxic chemotherapy have also been used for unresectable or recurrent disease. All treatment modalities carry an associated morbidity. We believe that the natural history of aggressive fibromatosis may include a period of stable disease without progression, during which time, treatment is not always necessary. Patients and methods. We present a retrospective review of 42 patients referred to the Royal Marsden Hospital between 1988 and 1995 with aggressive fibromatosis. Evidence of periods of stable disease and the relationship to delivered treatment was obtained from the case notes, including the natural history prior to referral to our institution. Stable disease was defined as a period of no objective progression for 6 months or longer. Results. Seventeen patients could be assessed for stable disease and all (100%) experienced at least one episode of stable disease, eight of whom whilst receiving hormonal or cytotoxic therapy. Of the 23 patients who could not be assessed for stable disease, as they underwent surgery at presentation or recurrence of disease, only 2 had persisting disease at last follow-up. Both of these patients had had positive surgical resection margins. Discussion. This study demonstrates the variable natural history of AF, which can include a substantial period of stable disease in a significant number of patients. A less aggressive approach to the management of AF may therefore be appropriate, particularly if a subgroup of patients who are likely to experience a period of stable disease can be identified.